Applications and techniques in information security : 10th International Conference, ATIS 2019, Thanjavur, India, November 22-24, 2019, Proceedings /: 10th International Conference, ATIS 2019, Thanjavur, India, November 22-24, 2019, Proceedings. (2019) - Unknown
No abstract available